BERPIKIR KRITIS ALA GENERASI Z DI ERA DISRUPSI DIGITAL - Tunjung Wijanarka (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2023)
In the present era of digital disruption, the advent of freedom of information has revolutionized people’s social lives. Communities now have easy access to creating, acquiring, and sharing information without undergoing prior verification. Consequently, this situation has given rise to unwise behaviors in the realm of social media, such as readily accepting or producing fake news and hoaxes. Ultimately, fake news becomes highly perilous as it often contains political content that poses a threat to the diverse society of Indonesia. Thus, the fundamental ability to think critically becomes indispensable for every individual, especially digital citizens, to navigate and acquire information prudently. To adress this issue, the author aims to raise awareness about the significance of critical thinking among students from the Faculty of Social Sciences and Communication Sciences (FISKOM) in utilizing social media through the implementation of a focus group discussion (FGD) during the 2023 Student Leaderhsip Basic Training (LDKM).